Atomic force microscopy–based study of self-healing coatings based on reversible polymer network systems. (January 2014) - Brancart, Joost; Scheltjens, Gill; Muselle, Thibault; Van Mele, Bruno; Terryn, Herman; Van Assche, Guy
A self-healing polymer system is created by incorporating reversible covalent bonds into an epoxy–amine-based network structure. The self-healing concept is based on the reversible Diels–Alder reaction between furan and maleimide functional groups. The thermal and mechanical properties of the reversible network structure are tailored in order to achieve good self-healing properties for the corrosion protection of metal surfaces. Atomic force microscopy is proposed as a technique to study the self-healing behavior of coatings. Local thermal analysis techniques are used to study the local thermomechanical behavior of the reversible network. Nanosized defects in the coatings are made by means of nanolithography. The actual self-healing behavior is studied by atomic force microscopy imaging before and after the heating steps. The healing capability of elastomeric and glassy model systems is compared.